Tilting of Foldable PCIOL Masquerading as Malignant Glaucoma - Gupta , Shakun (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
Two females reported to our Glaucoma Clinic with complaints of blurred vision & pain along with signs suggestive of malignant glaucoma post phacoemulsification cataract surgery with foldable PCIOL, operated elsewhere. B-scan showed posterior segment within normal limit, so ruled out suprachoroidal haemorrhage. I treated them first with YAG peripheral iridotomy (PI) & peripheral anterior hyaloidotomy through peripheral PI with antiglaucoma medications (AGM) & topical Atropine assuming the case to be of malignant glaucoma. But in follow up, anterior chamber (AC) was found to be shallow with one haptic of foldable IOL in sulcus tilting forward seen in dilated pupil under the effect of topical atropine responsible for causing condition masquerading as malignant glaucoma. Then, the cases were treated by redialing of foldable PCIOLs in bag in both the cases. Post redialing, there was improvement of visual acuity along with reformation of AC with normal depth & intraocular pressure (IOP) was also under control without AGM.